2021
DOI: 10.3390/nu13010203
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds for Skin Health: A Review

Abstract: Human skin is continually changing. The condition of the skin largely depends on the individual’s overall state of health. A balanced diet plays an important role in the proper functioning of the human body, including the skin. The present study draws attention to bioactive substances, i.e., vitamins, minerals, fatty acids, polyphenols, and carotenoids, with a particular focus on their effects on the condition of the skin. The aim of the study was to review the literature on the effects of bioactive substances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(142 citation statements)
references
References 217 publications
0
89
0
16
Order By: Relevance
“…Se is an essential trace element that participates in antioxidant defense and redox state regulation [119]. Some authors have shown that Se delays skin aging by protecting keratinocyte stem cells against UVAinduced cytotoxicity [120]. Supplementation with Se resulted in partial improvement in OLP patients; the improvement was similar with both topical and systemic Se and similar to that obtained with topical corticosteroids.…”
Section: Nutraceuticals As Antioxidantsmentioning
confidence: 81%
“…Se is an essential trace element that participates in antioxidant defense and redox state regulation [119]. Some authors have shown that Se delays skin aging by protecting keratinocyte stem cells against UVAinduced cytotoxicity [120]. Supplementation with Se resulted in partial improvement in OLP patients; the improvement was similar with both topical and systemic Se and similar to that obtained with topical corticosteroids.…”
Section: Nutraceuticals As Antioxidantsmentioning
confidence: 81%
“…It is emphasized that Cu stimulates the proliferation of skin fibroblasts. It is a cofactor of superoxide dismutase and also prevents lipid peroxidation and oxidative damage to cell membranes [71].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, minerals such as copper, zinc, and selenium also play important roles in skin health [ 19 , 153 , 154 ]. They are cofactors in enzymatic reactions during collagen crosslinking and necessary elements for epidermal proliferation and keratinocyte differentiation [ 154 , 155 ].…”
Section: Efficacy and Mechanisms Of Dietary Components In Mitigating Skin Photoaging: Animal And Human Evidencementioning
confidence: 99%